ANÁLISIS DEL PROCESO INCLUSIVO DEL ALUMNO CIEGO EN CLASES DE FÍSICA MODERNA - ROBERTO NARDI; EDER PIRES DE CAMARGO; EDVAL RODRIGUES DE VIVEIROS (Universidad Distrital Francisco José de Caldas, 2012)
This paper is aimed at understanding which the most important difficulties and alternatives to include students with visual impairments in physics classes. It presents and discusses the difficulties and viabilities of having a born blind student effectively attend Modern Physics classes. Using content analysis,this experiment identifies 6 functional classes that might correspond to difficulties and 4 which refer to the viabilities. Therefore, the importance of appropriate communicative environments, the including role of the interactivity element, as well as the need for Destitution of segregation environments inside classroom, are emphasized.